1987
DOI: 10.1042/bj2450423
|View full text |Cite
|
Sign up to set email alerts
|

The separation of glutathione transferase subunits by using reverse-phase high-pressure liquid chromatography

Abstract: A simple method is described for the separation and quantification of the subunits of GSH transferases present in rat tissue extracts. This method, involving GSH-agarose affinity chromatography followed by reverse-phase h.p.l.c., is rapid and sufficiently sensitive to measure 5 micrograms of each subunit in a mixture. Examples are given of its application to extracts of rat kidney, adrenal, testicular interstitial cells and seminiferous tubules. The analysis of seminiferous tubules indicates that the technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(79 citation statements)
references
References 29 publications
5
74
0
Order By: Relevance
“…Individual peaks were identified as GST subunits as shown in Figure 1 by SDS\PAGE, and immunoblotting with anti-GST antibodies (results not shown). The elution pattern of SD rat liver GSTs ( Figure 1A) was consistent with previous reports [34,35]. However, in the case of HHR liver GSTs ( Figure 1B), instead of subunit 3, a peak named X was detected between GST subunits 3 and 4.…”
Section: Different Elution Patterns Of Gst Subunits Between Hhr and Ssupporting
confidence: 90%
See 1 more Smart Citation
“…Individual peaks were identified as GST subunits as shown in Figure 1 by SDS\PAGE, and immunoblotting with anti-GST antibodies (results not shown). The elution pattern of SD rat liver GSTs ( Figure 1A) was consistent with previous reports [34,35]. However, in the case of HHR liver GSTs ( Figure 1B), instead of subunit 3, a peak named X was detected between GST subunits 3 and 4.…”
Section: Different Elution Patterns Of Gst Subunits Between Hhr and Ssupporting
confidence: 90%
“…Individual GST subunits were separated by HPLC, essentially as described by Ostlund-Farrants et al [34]. HPLC was carried out using a TSK-Gel Octadecyl-4PW column (4.6 mmi150 mm ; Tosoh, Tokyo, Japan).…”
Section: Separation Of Gst Subunits and Gsh By Hplcmentioning
confidence: 99%
“…Reversed-phase HPLC analysis of af nitypuri ed GST was performed by the method of Ostlund Farrants et al (23) with an HPLC-Kontron system equipped with a rheodyne injector and a photodiode variable-wavelength detector. Samples of GST were injected onto a reverse phase column Vydak 201 TP 5 (200 £ 3 mm) (Chrompack, Middelburg, The Netherlands) that had been equilibrated with 35% acetonitrile in 0.1% (v/v) tri uoroacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…DISCUSSION H.p.l.c. data revealed that two GST Alpha isoenzymes are present in human liver and kidney tissue [5,7]. Recently, we showed that the kidney isoenzymes, al and a2, have retention times similar to the two liver forms, referred to as ax and ay [5].…”
Section: Pgth2mentioning
confidence: 96%
“…analysis demonstrates two GST Alpha subunits in liver and kidney, referred to as a. and ay or a, and a2 respectively; the former is more basic than the latter [5,7], the pl being 8.9 for al and 8.4 for a2 [1].…”
Section: Introductionmentioning
confidence: 99%